Mechanisms of Formation of Structural Variation in a Fully Sequenced Human Genome. Issue 2 (19th November 2012) - Pang, Andy Wing Chun; Migita, Ohsuke; MacDonald, Jeffrey R.; Feuk, Lars; Scherer, Stephen W.
<x xml:space="preserve">Abstract</x> We examined breakpoint junction sequences to infer the formation processes of 408, 532 gains, 383, 804 losses and 166 inversions identified in the Venter (HuRef) genome. We noticed a differential proportion of mechanisms according to size. Ligation and replication slippage were prevalent for small variants, whereas larger variants were associated with retrotransposition and nonalleleic homologous recombination. By characterizing the full spectrum of variants and comparing with earlier studies, this work should represent the closest estimate of the true proportion of mutational processes in the genome. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>